Xanthogranulomatous cystitis presenting as hematuria: A case report and review of literature - Gupta, Rahul; Mahajan, Arti; Kapoor, Bharat Bhushan (Indian Journal of Case Reports, 2018)
Xanthogranulomatous cystitis (XC) is a rare benign chronic granulomatous inflammation of the urinary bladder of unknownetiology. Here, we report a rare case of XC in a 54-year-old man who presented with painless hematuria and frequent urinationfor the past 3 years. His urine culture and sensitivity were positive for Escherichia coli with significant colony count. Contrastenhancedcomputed tomography showed diffusely thickened urinary bladder with no definitive mass. The patient was subjected toother investigations including cystoscopy and biopsy. All the above investigations confirmed the entity to be XC. An endoscopicresection was performed and he was started on a sulfamethoxazole-trimethoprim combination. The patient was asymptomatic at3-month follow-up.